2000
DOI: 10.1046/j.1365-2672.2000.01150.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiology and taxonomy of Thiobacillus strain TJ330, which oxidizes carbon disulphide (CS2)

Abstract: A bacterium (strain TJ330) capable of using carbon disulphide (CS 2 ) as its sole energy source in an acidic environment was isolated from a peat bio®lter used in experiments to remove CS 2 and hydrogen sulphide (H 2 S) from air. Its physiology and taxonomy are described here. The strain oxidized CS 2 , H 2 S and elemental sulphur to sulphate chemolithotrophically. The rate of sulphate production was highest at pH 2. The maximum growth rate constant (m max ) using CS 2 as a substrate was 3Á9 Â 10 À2 h À1 (gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
0
10
1
Order By: Relevance
“…We also observed fungal growth at 6% H 2 SO 4 (pH Ϫ0.05) in our enrichment cultures but did not further investigate the species present in these cultures. With growth at pH as low as Ϫ0.05 (6% H 2 SO 4 ), the new Acidithiobacillus isolates obtained in this research exceed the previously reported pH limit of 0.5 for microbial CS 2 conversion for Acidithiobacillus TJ330 (9).…”
Section: Discussioncontrasting
confidence: 52%
See 2 more Smart Citations
“…We also observed fungal growth at 6% H 2 SO 4 (pH Ϫ0.05) in our enrichment cultures but did not further investigate the species present in these cultures. With growth at pH as low as Ϫ0.05 (6% H 2 SO 4 ), the new Acidithiobacillus isolates obtained in this research exceed the previously reported pH limit of 0.5 for microbial CS 2 conversion for Acidithiobacillus TJ330 (9).…”
Section: Discussioncontrasting
confidence: 52%
“…Furthermore, the enrichments and isolated Acidithiobacillus strains could grow at very high H 2 SO 4 concentrations. The only acidophilic CS 2 -converting Acidithiobacillus strain described to date, TJ330, was isolated from an acidic (pH 6.1 to 1.4) CS 2 -and H 2 S-treating peat biofilter (9). The neutrophilic CS 2 -converting species Paracoccus denitrificans was isolated from oak leaves and soil beneath the leaf canopy (7,27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several bacterial species that can grow chemolithoautotrophically on CS 2 at neutral pH have been identified from soil, sludge, and freshwater habitats (8)(9)(10)(11)(12). At acidic pH, so far only some (Acidi)thiobacillus strains, isolated from hot springs and volcanic areas, were shown to be able to use CS 2 (8,13). Acidophilic Acidithiobacillus thiooxidans strains are currently in use in biotrickling filters (6,(14)(15)(16), due to the inherent acidification of the trickling filter upon growth on CS 2 .…”
mentioning
confidence: 99%
“…The mean degradation rates ranged from 0.12 to 1.28 mg h −1 depending on the CS 2 mass flux applied in the experiments. Microbial degradation of CS 2 under aerobic and anaerobic conditions has been studied in the field of waste-gas treatment (e.g., Smith and Kelly, 1988;Hartikainen et al, 2000;Pol et al, 2007). They found microbes of the Thiobacillus species able to oxidize CS 2 under certain conditions.…”
Section: Retardation Of Csmentioning
confidence: 99%